Trace of evil - Blanchard, Alice (Blanchard, Alice. Natalie Lockhart, 2019)
"There's something wicked in Burning Lake... Natalie Lockhart is a rookie detective in Burning Lake, New York, an isolated town known for its dark past. Tasked with uncovering the whereabouts of nine missing transients who have disappeared over the years, Natalie wrestles with the town's troubled history - and the scars left by her sister's unsolved murder years ago. Then Daisy Buckner, a beloved schoolteacher, is found dead on her kitchen floor, and a suspect immediately comes to mind. But it's not that simple. The suspect is in a coma, collapsed only hours after the teacher's death, and it turns out Daisy had secrets of her own. Natalie knows there is more to the case, but as the investigation deepens, even she cannot predict the far-reaching consequences - for the victim, for the missing of Burning Lake, and for herself"--